2003
DOI: 10.1074/jbc.m300763200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Hypoxia-inducible Factor-1α Protein Level during Hypoxic Conditions by the Phosphatidylinositol 3-Kinase/Akt/Glycogen Synthase Kinase 3β Pathway in HepG2 Cells

Abstract: Hypoxia initiates an intracellular signaling pathway leading to the activation of the transcription factor hypoxia-inducible factor-1 (HIF-1). HIF-1 activity is regulated through different mechanisms involving stabilization of HIF-1␣, phosphorylations, modifications of redox conditions, and interactions with coactivators. However, it appears that some of these steps can be cell type-specific. Among them, the involvement of the phosphatidylinositol 3-kinase (PI3K)/Akt pathway in the regulation of HIF-1 by hypox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
230
3
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 292 publications
(257 citation statements)
references
References 50 publications
19
230
3
3
Order By: Relevance
“…Additionally, it is well known that AKT regulates glycogen synthesis through phosphorylation at Ser9 followed by inactivating the GSK3β. When the cells are exposed to hypoxic conditions, time-dependent biphasic HIF1α stabilization and activation by PI3K/AKT/GSK3β signaling pathway has been proposed but this explanation remains controversial (50). Our present results supported part of the initial response reported in previously findings (50), although the hypoxic treatment of the cells with a different type of PIK3CA mutation was for a longer time compared with that in the previous report (50).…”
Section: Expression Of Several Proteins Related To Glycogen Metabolissupporting
confidence: 80%
See 1 more Smart Citation
“…Additionally, it is well known that AKT regulates glycogen synthesis through phosphorylation at Ser9 followed by inactivating the GSK3β. When the cells are exposed to hypoxic conditions, time-dependent biphasic HIF1α stabilization and activation by PI3K/AKT/GSK3β signaling pathway has been proposed but this explanation remains controversial (50). Our present results supported part of the initial response reported in previously findings (50), although the hypoxic treatment of the cells with a different type of PIK3CA mutation was for a longer time compared with that in the previous report (50).…”
Section: Expression Of Several Proteins Related To Glycogen Metabolissupporting
confidence: 80%
“…5B). Since PIK3CA gene mutation causes the continuous activation of AKT, it was not surprising in HAC2 cells that the phosphorylated AKT at Ser473 was elevated under hypoxic culture conditions as well as DFO treatment, moreover, the stabilized HIF1 (48,49) was further activated by PI3K/AKT pathway, one of the main mechanisms of HIF1 activation, as reported previously (50). Additionally, it is well known that AKT regulates glycogen synthesis through phosphorylation at Ser9 followed by inactivating the GSK3β.…”
Section: Expression Of Several Proteins Related To Glycogen Metabolismentioning
confidence: 53%
“…We identified three novel genes previously unknown to play a role in the C. elegans HIF pathway. Two of these, spe-8 and gska-3, are predicted homologues of the human tyrosine kinase FER and the serine/threonine glycogen synthase kinase GSK-3 respectively, which have previously been reported to play a role in HIF regulation in mammalian cells (Mottet et al, 2003;Salem et al, 2005). Using gska-3-deficient animals, we confirmed increased hypoxia sensitivity observed with gska-3 knockdown.…”
Section: Twist1 Is a Target Of Hif-2a Eh Gort Et Alsupporting
confidence: 72%
“…Several studies also suggested that Act significantly contributes to HIF-1a stabilization. 31,32 A direct role of FOXP1 in HIF regulation cannot however, be excluded as a recent study indicated that the nuclear FOXO4 protein downregulates HIF-1a through prolyl hydroxylase/pVHL-independent transcriptional pathway. 33 The biological consequences of the cytoplasmic localization of FOXP1 or its overall loss of expression are obscure.…”
Section: Discussionmentioning
confidence: 99%